KORELASI ANTARA BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMP ISLAM TERPADU IMAM SYAFI’I KECAMATAN NONGSA KOTA BATAM KEPULAUAN RIAU - Aziz, Muhammad; Ari Supadi, Suharto; Yasin, Muhammad (UNISAN JURNAL, 2024)
This study aims to prove the Influence of Culture and Work Motivation on Teacher Performance in Madrasah Tsanawiyah Darul Hijrah Walfallah Babat Supat, Babat Supat District, Musi Banyuasin Regency. This research is a quantitative research research using quantitative research methods by using questionnaires as instrument of research data collection and interview methods to find out how the culture and work motivation of teacher performance in Madrasah Tsanawiyah Darul Hijrah Walfallah Babat Supat, Babat Supat District, Musi Banyuasin Regency. The results of this study found that: 1) in the r product moment table in significance levels of 1% and 5%. For N = 37 at a significant level of 5% = 0.325 so that r count greater than r table means that there is a significant influence and a significant level of 1% = 0.418 is smaller than r count so there is a significant influence.